Nurses' hemovigilance knowledge and performance after teach-back, concept map, and lecture: A quasi-experimental study. Issue 1 (January 2021) - Masror Roudsari, Daryadokht; Feizi, Shahoo; Maghsudlu, Mahtab
Abstract: Objectives: This study aimed to compare the effects of teaching by three methods of teach-back, concept map, and lecture on knowledge and performance of nurses in hemovigilance process. Methods: This quasi-experimental study was performed on 108 Iranian nurses. In the lecture group, the educational intervention was conducted during a 4-hour session; and in the concept map and teach-back groups, it was performed in two 2-hour sessions. The nurses' knowledge and performance were measured by "routine blood transfusion knowledge questionnaire (RBTKQ)" and "self-reporting performance-evaluator questionnaire". Results: After the interventions, knowledge was significantly higher in the teach-back and the concept map groups compared to the lecture group (p = 0.001), but the performance in the lecture group was higher than the other two groups (p = 0.01). No statistically significant differences were found between teach-back and concept map groups. Conclusion: Teach-back and concept map methods were effective in improving the nurses' hemovigilance knowledge, while the lecture was associated with a significant increase in their performance. Therefore, integrating the hemovigilance teaching methods is suggested. Abstract : Blood safety; Hemovigilance, Knowledge; Teaching; Nurses; Work performance.